Analysis of the influence of bank health level using RGEC method, dividend payout ratio, and company size on profitability in Sharia commercial bank in Indonesia and Malaysia - Sugiharto, Bambang; Handayani, Asri (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to analyze the influence of the level of bank health using the RGEC method (Risk Profile, Good Corporate Governance, Earning and Capital), Dividend Payout Ratio, and Company Size on profitability in Islamic commercial banks in Indonesia and Malaysia. Meanwhile, Risk Profile is measured using the Financing to Deposit Ratio (FDR), Good Corporate Governance is measured using self-assessment, Earning is measured using the ratio of Operational Expenses to Operational Income (BOPO), and Capital is measured using the Capital Adequacy Ratio (CAR). The data used comes from financial reports and GCG reports published on the websites of each Islamic bank. The population used in this research is Indonesian sharia commercial banks and Malaysian sharia commercial banks, totaling 145 sharia commercial banks. The sampling technique used was purposive sampling. There are 35 samples which are outlier data. The analytical method used in this research is multiple regression analysis. The research results show that Good Corporate Governance (GCG), Capital Adequacy Ratio (CAR), and Dividend Payout Ratio (DPR) have a positive effect on profitability, while Financing to Deposit Ratio (FDR), Operational Expenses to Operating Income (BOPO), and Size The company has a negative effect on profitability.